Training on Optimizing Digital Marketing Management for MSME Entrepreneurs to Enhance Business Competitiveness in the Digital Economy Era - Talenta Emma Renata Marbun; Erlianti Simanjuntak; Benyamin Nababan; Nani D. S. Sihombing; Miranda Silvia Prastka Pasaribu (Yayasan Rahmat Islamiyah, 2026)
The development of the digital economy requires micro, small, and medium enterprises (MSMEs) to manage technology-based marketing in a more structured manner. Many MSMEs have used social media and messaging applications, yet their use often remains spontaneous, lacks consumer segmentation, has inconsistent brand identity, and is not supported by measurable marketing evaluation. This community service activity aims to provide counseling on optimizing digital marketing management for MSME actors to improve business competitiveness in the digital economy era. The activity used a participatory-educative approach through needs identification, material delivery, discussion, content preparation simulation, practical use of social media and WhatsApp Business, and participant understanding evaluation. The counseling materials covered digital marketing concepts, target market identification, brand identity strengthening, promotional content creation, customer interaction management, marketplace utilization, and digital marketing performance indicators. The results indicate that counseling can strengthen digital literacy, especially by helping MSME actors understand that digital marketing is not merely uploading product photos, but a managerial process involving planning, implementation, control, and follow-up. This activity recommends further mentoring so that MSMEs can implement digital marketing action plans consistently and measurably.